Paediatric and adolescent alveolar soft part sarcoma: A joint series from European cooperative groups. Issue 11 (16th July 2013) - Orbach, D.; Brennan, B.; Casanova, M.; Bergeron, C.; Mosseri, V.; Francotte, N.; Van Noesel, M.; Rey, A.; Bisogno, G.; Pierron, G.; Ferrari, A.
Abstract Background Alveolar soft part sarcomas (ASPS) are generally chemo‐ and radio‐resistant mesenchymal tumours, with no standardized treatment guidelines. We describe the clinical behaviour of paediatric ASPS and compare these features to previously reported adult series. Patients and Methods The clinical data of 51 children and adolescents with ASPS, prospectively enrolled in or treated according to seven European Paediatric trials were analysed. Results Median age was 13 years [range: 2–21]. Primary sites included mostly limbs (63%). IRS post‐surgical staging was: IRS‐I (complete resection) 35%, II (microscopic residual disease) 20%, III (gross residual disease) 18% and IV (metastases) 27%. Only 3 of the 18 evaluable patients (17%) obtained a response to conventional chemotherapy. After a median follow‐up of 126 months (range: 9–240), 14/18 patients with IRS‐I tumour, 10/10 IRS‐II, 7/9 IRS‐III and 2/14 IRS‐IV were alive in remission. Sunitinib treatment achieved two very good partial responses in four patients. Ten‐year overall survival (OS) and event free survival (EFS) was 78.0 ± 7% and 62.8 ± 7% respectively. Stage IV, size >5 cm and T2 tumours had a poorer outcome, but only IRS staging was an independent prognostic factor. Conclusions ASPS is a very rare tumour frequently arising in adolescents and in the extremities, and chemo resistant. Local surgical control is critical. ASPS is a poorly chemo sensitive tumour. For IRS‐III/IV tumours, delayed radical local therapies including surgery are essential. Metastatic patients had a poor prognosis but targeted therapies showed promising results. Pediatr Blood Cancer 2013;60:1826–1832. © 2013 Wiley Periodicals, Inc.